Modeling of Etching Nano-surfaces of Indium Phosphide - S.L. Khrypko; V.V. Kidalov; E.V. Kolominska (Журнал нано- та електронної фізики)
This paper describes a mechanism for obtaining a regular porous structure InP, which is to use the method of photoelectrochemical etching. Through the use of simulation etching at the nanoscale, it is possible to get a regular uniform grid of nanopores on the surface of indium phosphide, which allows us to understand the mechanisms and the establishment of technological regimes anodic structures indium phosphide to produce a variety of devices.